2005
DOI: 10.1093/brain/awh494
|View full text |Cite
|
Sign up to set email alerts
|

Three to four years after diagnosis: cognition and behaviour in children with ‘epilepsy only’. A prospective, controlled study

Abstract: A 3.5-year follow-up study of cognition and behaviour in 42 children with newly diagnosed idiopathic or cryptogenic epilepsy ('epilepsy only') attending mainstream education and 30 healthy gender-matched classmate controls was carried out to identify differences between groups, to detect factors that contribute to the difference and its change over time, and to establish the proportion of poorly performing children. The neuropsychological battery covered the major domains of cognition, mental and motor speed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
85
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 27 publications
8
85
0
3
Order By: Relevance
“…The results of our study further elaborate this theoretical framework by showing support for modified models (Figure 1-B) that include the interaction of specific family and early child characteristics with later behavior problems. Early behavior problems in children with epilepsy are one of the best predictors of behavior problems later in childhood [9]. Therefore, it is important that we identify children with behavior problems at the onset of seizures to try to prevent future behavioral maladjustment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our study further elaborate this theoretical framework by showing support for modified models (Figure 1-B) that include the interaction of specific family and early child characteristics with later behavior problems. Early behavior problems in children with epilepsy are one of the best predictors of behavior problems later in childhood [9]. Therefore, it is important that we identify children with behavior problems at the onset of seizures to try to prevent future behavioral maladjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Children with epilepsy have been shown to be at increased risk for psychopathology [2,3] as well as for problems with adjustment, including behavior, and cognition [4][5][6][7][8][9]. Children with seizures are up to 4.7 times more likely to have behavior problems than control children [4,8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover individuals with epilepsy tend to discontinue education early due to disability, or show poor scholastic performance due to cognitive decline. 39,47,50 Earlier studies have not included occupation and Socio-Economic class as variables. This study shows that subjects belonging to the lower Socio-Economic group and having unskilled labour have cognitive impairment when compared to subjects in the middle and upper economic class.This study included marital status, domicile and type of family as socio-demographic variables, these variables did not have any statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…5 Patients with idiopathic generalized epilepsy performed significantly poorer in non-verbal and verbal attention, verbal learning and memory, word fluency, and controlled sequential fine motor responses excluding non-verbal memory. 47,50,51 Patients with idiopathic generalized epilepsy, early seizure onset prior to 18 years was a powerful predictor of neuropsychological impairment. 7,8,52 There are several reports about the cognitive impairment and cognitive deterioration in patients with epilepsy.The research data indicate that the cognitive impairment and deterioration are due to associated brain damage and not attributable to Epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…They did not obtain specific measures of each child's academic performance. The final study by Oostrom and colleagues (27,29) compared children enrolled in regular school classrooms who had experienced two or more unprovoked idiopathic or cryptogenic seizures within the past year with gender-matched classmate normal controls. They found that children with epilepsy scored significantly worse on academic skills (reading, writing, and math) than controls and, over the year following entry into the study, a decline in these skills was found.…”
mentioning
confidence: 99%